Establishment of an induced pluripotent stem cell (iPSC) line (JNMUi002-A) from a male patient with schizophrenia - Meixiang Jiang; Yuxing Long; Yiliang Liu; Ran Li; Jingyi Xu; Tongyue Chi; Menglu Sun; Miao Li; Hao Yu; Lu Yu; Xiaobo Han (Stem Cell Research)
We obtained Peripheral blood mononuclear cells (PBMCs) from a peripheral blood sample of a 19-year-old male schizophrenia patient and successfully established induced pluripotent stem cell (iPSC) line using non-integrated reprogramming technology. This cell line possesses the correct karyotype, shape of an embryonic stem cell, the ability to express particular pluripotency markers, and the capacity to differentiate into three germ layers in vitro. This cell line will serve as an in vitro model for upcoming studies on the etiology of schizophrenia and the creation of novel treatment.